If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying G = 7b(r + -8) Reorder the terms: G = 7b(-8 + r) G = (-8 * 7b + r * 7b) G = (-56b + 7br) Solving G = -56b + 7br Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Simplifying G = -56b + 7br
| 77-3X=-56-7X | | 2X+12=-36-6X | | 1-w-w^2=0 | | 3x+p=q | | 4w^4+9m^2= | | 747-60h=747 | | 1x^2-17x+42=0 | | (x+6)(x+2)=(2x-2)(x+4) | | x+5=(x+5) | | 2X+20=6X+11 | | x+5=(x+5)2 | | 747-60h=300 | | d=a+b+cforb | | 5=x+25x+25 | | 0.65x+0.05(16-x)=0.10(-28) | | (x+6)(x-3)=(2x+5)(x-3) | | x+25x=5 | | 0.16x-x^3= | | x=25x+20 | | (3x+8)(x-4)=12x+32 | | 2.564x=12.46104 | | 3y+3x=-3y+17x | | 3x+3y=-3x+17y | | 9n^8-16p^2= | | 2(-1)-5= | | -2.7=3.3-3y | | 9x^2+24xy+16y^2= | | y=-2x^2+4x+70 | | x=61200+x(1.04) | | (3y+2)(y+7)=-4(3y+2) | | .5x+.6x=40-3x | | -5x-4y=16 |